2014
DOI: 10.1080/0092623x.2014.966397
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Beliefs of Turkish Men: Comparing the Beliefs of Men With and Without Erectile Dysfunction

Abstract: Sexual beliefs underlying male sexual dysfunction are known to emphasize excessively high sexual performance, among other inaccuracies. The purpose of this study was to determine the frequency of certain sexual beliefs among Turkish men with and without erectile dysfunction. In this comparative-descriptive study, demographic data and participant views regarding 50 common sexual beliefs were collected with a questionnaire. The study was conducted at the urology clinic of a university hospital in Turkey between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…While Nobre and colleagues (2005) demonstrated the relationship between these constructs in a Portuguese sample, these results have been replicated across other cultural samples as well. For example, the relationship between men with ED and belief in these themes were further demonstrated in a Turkish sample (Apay et al, 2015). In addition, Nelson and Purdon (2011) found that men with performance related fears are more likely to report experience sexual difficulties, including ED.…”
Section: Bss and Edmentioning
confidence: 89%
“…While Nobre and colleagues (2005) demonstrated the relationship between these constructs in a Portuguese sample, these results have been replicated across other cultural samples as well. For example, the relationship between men with ED and belief in these themes were further demonstrated in a Turkish sample (Apay et al, 2015). In addition, Nelson and Purdon (2011) found that men with performance related fears are more likely to report experience sexual difficulties, including ED.…”
Section: Bss and Edmentioning
confidence: 89%
“…Medeni durum açısından evli ve bekar katılımcılar arasında mükemmeliyetçilik puanları açısından anlamlı bir farklılık görülmezken, evli bireylerin cinsel mitlere inanma düzeyi bekar bireylerden daha yüksek bulunmuştur. Mükemmeliyetçiliğin medeni durum açısından evli bireyler lehine farklılık gösterdiğini bildiren çalışmaların (Kiremitci, Gençer ve Demiray, 2014) yanı sıra araştırma sonucunu destekleyen ve mükemmeliyetçiliğin medeni duruma göre anlamlı farklılık göstermediğini belirten çalışmalar da bulunmaktadır (Erdoğan, Topuz ve Bahadır, 2018). Medeni durumun mükemmeliyetçilik açısından belirleyici bir değişken olmaması, mükemmeliyetçiliğin durum odaklı olmaktan ziyade bir kişilik özelliği olarak değerlendirilmesiyle açıklanabilmektedir (McArdle, 2010).…”
Section: Cinsel Mitler öLçeği (Cmö)unclassified
“…Sexuality is a complex and dynamic process that exists in life from childhood to old age ( 16 ). Sexual health is associated with both physical and mental well-being ( 17 ). The meaning attributed to sexuality and the concept of sexual health is significantly influenced by religious rules, prejudices, taboos, traditions, and customs.…”
Section: Introductionmentioning
confidence: 99%